2006
DOI: 10.1111/j.1748-7692.2006.00056.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of Diving by Harbor Seal Pups in Two Regions of Alaska: Use of the Water Column

Abstract: Satellite-linked dive recorders were attached to 53 harbor seal pups in Prince William Sound (PWS) and at Tugidak Island, Alaska, during 1997-1999. We used generalized additive models and bootstrap techniques to describe pup diving behavior during their first year of life. Pups increased their ability to dive during the first 3-6 mo, as indicated by increases in proportion of time in the water (time wet) and maximum dive depth achieved by a pup each day (max-depth) values. Time wet and/or max-depth later decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 87 publications
1
4
1
Order By: Relevance
“…However, rerunning our analyses with variations in these parameters had no affect on our general conclusions. We also note that Frost et al (2006), reported a maximum “wet time” between 86% and 88% for juvenile harbor seals, a figure in accord with the PD 90 values in this study.…”
Section: Discussionsupporting
confidence: 90%
“…However, rerunning our analyses with variations in these parameters had no affect on our general conclusions. We also note that Frost et al (2006), reported a maximum “wet time” between 86% and 88% for juvenile harbor seals, a figure in accord with the PD 90 values in this study.…”
Section: Discussionsupporting
confidence: 90%
“…This suggests that as pups age, those that perform more HID generally also have higher Hct, Hb, MCH and MCV values. Unlike previous studies, which indicate that depth drives dive duration, hypoxia [ 1 , 15 , 62 , 63 ] and subsequently the production of more, large RBC, [ 20 , 58 ] this study indicates that hematological parameters may be driven by frequent periods of extended apnea without an increase in depth. Since these parameters were not significantly affected by maximum dive duration or mean dive duration in the models, it can be inferred that the frequency of long-duration dives as opposed to depth, may drive this process in captivity.…”
Section: Discussioncontrasting
confidence: 86%
“…A similar trend was observed in wild harbor seal pups, [ 1 , 15 , 25 ] though wild pups were recorded to dive deeper and for longer periods of time at a younger age (8 min, age 1 week: [ 61 ]; approximately 9 minutes, age under 12 days:[ 25 ]; 8.5 min, age under 25 days: [ 1 ]; 3.6 min, under 25 days: [ 15 ]) than the captive pups in this study (maximum 13.6 min at 89 days, maximum under 25 days: 2.68 min). Harbor seal pup dive durations may be dependent on available depth in the water column [ 1 , 15 , 62 , 63 ] and pup motivation [ 63 ]. This study suggests that although the pool depth may affect the rate of development of these skills, it does not impede pups from performing long duration dives.…”
Section: Discussionmentioning
confidence: 99%
“…Otariids have longer dependency periods and, therefore, increased opportunities for maternal transfer of knowledge. Although some researchers have assumed mothers and their dependent young dive and forage together (Pitcher and Calkins 1981, Loughlin et al 2003, Frost et al 2006) and others have assumed they do not (Atkinson 1997, Trillmich and Weissing 2006), no prior studies have directly investigated otariid mother‐pup associations at sea. The Australian sea lion, Neophoca cinerea , demonstrates one of the longest lactation periods in pinnipeds (17.6 mo: Higgins and Gass 1993), and pups begin diving before they are weaned (Fowler et al 2006).…”
mentioning
confidence: 99%